Efficient real estate market in Poland - Wiśniewski, Radosław (Economics and Business Review, 2008)
The information efficiency of the real estate market is its ability to fully and immediately reflect all significant information in real estate prices. Efficiency is understood as the continuous reflection of respective information entering the system in real estate transaction prices, assuming this information is known, understood and unconditionally part of the decision-making process. Efficiency may be defined on two levels. The first one relates to the organization effectiveness of market system structures. The other one is related to the precision with which the price established on the real estate market reflects the actual value of the real estate and also to its ability to respond to the continuous inflow of information. The paper presents the theory of real estate market efficiency and verifies the hypothesis that the information efficiency of the real estate market in Poland is insufficient. (original abstract)